An Extended ERP model for Yemeni universities using TAM model. (International Journal of Engineering and Computer Science, 2017)
The main problems had been discussed for a while are complexity and failure of ERP system in an institution. To solve these problems and reduce this complexity some researchers were concentrated on the effect of perceived usefulness (PU) and perceived ease of use (PEOU) on the attitude toward using enterprise resource planning (ERP) system based on the theory of technology acceptance model (TAM) whereas, others focus on studying critical success factors (CSFs). On the other side, limited researchers put them together to check the influence of critical success factors on PU and PEU, as a key factor for accepting ERP system. However, this paper focuses on studying these CSFs and its affection on Yemeni higher education institutions using an extended technology acceptance model (TAM). This paper analyzes the impact of CSFs on user attitude toward using ERP at Yemeni higher education institutions. The proposed model has thirteen constructs, and they are: 1. Vision and objectives (VO), 2. Top management support and commitment (TM), 3. Business process (BP), 4. Organizational structure (OS), 5. Budget size (BS), 6. Human resources management (HRM), 7. Project management (PM), 8. Training and education (TE), 9. Business process re-engineering (PRE), 10. Communication and connection (COM), 11. Perceived ease of use (PEOU) 12. Perceived usefulness (PU), 13. Attitude toward (AT) using ERP and sixteen hypotheses which was generated to study the relationship between these constructs. The present Partial Least Squares (PLS) involves these relationships based on a survey of 123 users to measure the acceptance of this model. Results suggest important applied attitude toward using ERP and to develop the understanding of how to implement this attitude in higher education institutions and also we find that understanding of user's perceived ease of use and user's perceived usefulness should be taken into consideration for an institution in pre-implementation stage of an ERP system especially at Yemeni higher education institutions.